2019
DOI: 10.1016/j.omtm.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Expansion of Anti-viral T Cells from Cord Blood by Accelerated Co-cultured Dendritic Cells

Abstract: Hematopoietic stem cell transplantation (HSCT) using unrelated cord blood (CB) donors is a suitable approach when an HLA-matched donor is not available. However, one important drawback is the risk of life-threatening viral infections prior to immune reconstitution, particularly from adenoviruses (AdVs). Although adoptive therapy with ex vivo expanded virus-reactive donor T cells has proven effective to treat these infections in HSCT recipients, the manufacturing process is complex and requires large numbers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…This, together with the efficient gas exchange and ready availability of abundant nutrients in culture medium, may explain the much more rapid and efficient expansion in G-Rex compared with T-flasks. G-Rex has been used by other groups for the optimal expansion of several types of blood cells, including tumor-infiltrating lymphocytes (TILs) [19,20], antigen-specific T cells [8,12,17,[33][34][35], gd T cells [23], Tregs [21,22], NKs [15], CIKs [25], CAR-Ts [16,24], megakaryocytes [36] and red blood cells [37] (reviewed in [9]). In most of these published cases, medium addition or exchange, as well as culture splitting, was performed with cell counting at various phases of the culture to define optimal dilution and collection times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, together with the efficient gas exchange and ready availability of abundant nutrients in culture medium, may explain the much more rapid and efficient expansion in G-Rex compared with T-flasks. G-Rex has been used by other groups for the optimal expansion of several types of blood cells, including tumor-infiltrating lymphocytes (TILs) [19,20], antigen-specific T cells [8,12,17,[33][34][35], gd T cells [23], Tregs [21,22], NKs [15], CIKs [25], CAR-Ts [16,24], megakaryocytes [36] and red blood cells [37] (reviewed in [9]). In most of these published cases, medium addition or exchange, as well as culture splitting, was performed with cell counting at various phases of the culture to define optimal dilution and collection times.…”
Section: Discussionmentioning
confidence: 99%
“…The G-Rex devices have been optimized for expansion of different types of T cells for research or clinical use [10,13,15,16]. Thus G-Rex devices have been used to produce antigen-specific T cells [8,12,17,18], tumor-infiltrating lymphocytes (TILs) [19,20], regulatory T cells (Tregs) [21,22], g/d T cells [23] and chimeric antigen receptor (CAR) T cells [16,24] as well as CIKs [25].…”
Section: Introductionmentioning
confidence: 99%
“…That includes peer-reviewed guides for CTL from PBMC [ 182 , 183 ] and UCB [ 184 ], NK cells [ 185 ], TILs [ 186 ] and CAR-T cells [ 157 ]. When comparing its yield, the expansion of T cells in the G-rex generates up to 100 [ 173 ] to 1000 [ 158 ] times more cells than classical static culturing techniques, but there are lower yield exceptions [ 175 , 177 ]. In the same way, NK cells and TILs have also shown better or similar expansion performance, but the difference is moderate [ 106 , 159 , 180 ].…”
Section: Comparison Of Currently Available Act Bioreactor Technologiementioning
confidence: 99%
“…In TILs, the Phenotype has been found to be similar to static systems [ 180 ], with no evidence for cloning selection [ 159 ]. Functionality-wise, T cells grown in the G-rex preserve their cytolytic activity [ 158 , 160 , 176 ] and some research have found better [ 177 ] to similar [ 162 ] cytokine expression profile compared to static controls. The cytokine production of TIL grown in G-rex flasks is similar to TIL produced with 24-well plates, T-175 flasks, and bags [ 180 ].…”
Section: Comparison Of Currently Available Act Bioreactor Technologiementioning
confidence: 99%
See 1 more Smart Citation